IFRS For Dummies - Collings, Steve (--For dummies., 2012)
The easy way to get a grip on International Reporting StandardsIFRS For Dummies is your complete introduction to IFRS and international accounting and balancing standards. Combining all the facts needed to understand this complex subject with useful examples, this easy-to-read guide will have you on top of IFRS in no time. In plain English, it helps you make sense of IRFS and your understanding of: what they are and where they apply; how to adopt IFRS for the first time; how IFRS affects the key components of your financial statements; how to disclose information in financial statements; and mu.